PENGARUH LITERASI KEUANGAN DAN PENGENDALIAN INTERNAL PADA KAS KECIL USAHA RUMAHAN - Mas Amah, Mas Amah; Hadli, Hadli; Ermeila, Sri (Taksasila Edukasi Insani, 2025)
This qualitative case study looks at how financial literacy and internal control affect petty-cash routines in 12 home-based microenterprises. Located along Jalan Politeknik, the study helps us understand the current efforts to improve financial practices in small and medium enterprises in Indonesia. We gathered data through semi-structured interviews, non-participant observations, and document checks. We then analyzed this data using cross-case thematic analysis. The findings show a clear relationship: the level of financial literacy—whether low, medium, or high—directly impacts how well petty-cash is managed. Effectiveness revolves around five key controls: fund separation, imprest limits, mandatory documentation, simple prior authorization, and scheduled reconciliation.The study's unique contributions are two practical tools, micro-authorization (quick approval along with immediate photo proof) and weekly reconciliation. These tools effectively reduce ongoing leakages common in family-run settings. The study provides practical guidance in a clear order for improving these practices, in line with national financial literacy policy directions. Keywords : Financial literacy in MSMEs, Internal control practices, Petty cash management, Weekly reconciliation routines, Micro-authorization and photo-proof